The Influence of the "Mading Pintar" Group Investigation Learning Model on Primary School Student Learning Outcomes - Ulfa, Maria; Dewi, Sri Enggar Kencana; Pertiwi, Ratih Purnama (Journal of Elementary Educational Research, 2024)
Abstract This research aims to see whether the "Mading Pintar" group investigation learning model positively impacts student learning outcomes. This research uses a quantitative approach, pre-experimental design, one-group pretest, and post-test design. Samples were taken using a purposive sampling technique. The data collection instrument was an unstructured interview sheet addressed to the homeroom teacher of class IV A with 8 questions to collect information. A test sheet with 14 questions was given to class IV A students to determine the learning outcomes of pretest and posttest students, and a Guttman scale questionnaire sheet with 15 questions, Yes (1 point )and No (0 points) was given to class IV A students to see the effectiveness of using the group investigation learning model. "Smart Mading". The validity and reliability test is an initial stage analysis with 20 questions before and 14 questions after being tested. The pretest normality test obtained a value of 0.017 < 0.05 and the posttest 0.000 < 0.05, indicating that the pretest and posttest values ​​were not normally distributed. Apart from that, the final stage analysis of the Wilcoxon test obtained a significance value of Asymp. sig.(2-tailed) 0.001 < 0.05 that the hypothesis was accepted. Meanwhile, the one sample t-test obtained 65.71%, including the "Effective" criteria. So it can be concluded that the "Mading Pintar" group investigation learning model can improve student learning outcomes and is effective for use in the learning process.